The Per Jacobsson Lecture : Asian Monetary integration; Will It Ever Happen? (per Jacobson lecture, 2006)
This paper discusses the need for Asian Monetary Integration. The original motivation for proposals for Asian monetary Integration had to do with a desire to reduce Asia's susceptibility to shocks, particularly financial shocks. There was also a broader sense that Asia had to be more self-reliant and gain fuller control over its destiny. The objectives are about growth, about greater trade integration, about spurring greater cross-border flows of investment within Asia, and about promoting the integration and deepening of financial markets. This paper highlights that financial market integration has lagged substantially behind trade integration, and this is why Asian saving surpluses are intermediated largely through financial markets outside Asia.